2002
DOI: 10.1159/000047989
|View full text |Cite
|
Sign up to set email alerts
|

The Winter Season Affects More Severely the Facial Skin than the Forearm Skin: Comparative Biophysical Studies Conducted in the Same Japanese Females in Later Summer and Winter

Abstract: Skin disorders such as atopic dermatitis, psoriasis and senile xerosis show a tendency to exacerbate in winter. We investigated the seasonal influence on the functional parameters of the skin in healthy female volunteers of different age groups. Biophysical noninvasive measurements, including transepidermal water loss (TEWL) as a parameter for the barrier function of the stratum corneum (SC), high-frequency conductance as a parameter for the hydration state of the SC, temperature, color and casual surface lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 28 publications
8
62
0
Order By: Relevance
“…The seasonal shift from summer to winter leads to an increase of TEWL and decreases the amount of water in the stratum corneum. 27,28 In our visual dryness rating of each subject's body and facial skin, most subjects showed no skin dryness or only a slight dryness in the summer (Table 5). However, the deterioration of skin dryness by the seasonal change to winter is considerably different between the high RR and the low RR groups.…”
Section: Discussionmentioning
confidence: 96%
“…The seasonal shift from summer to winter leads to an increase of TEWL and decreases the amount of water in the stratum corneum. 27,28 In our visual dryness rating of each subject's body and facial skin, most subjects showed no skin dryness or only a slight dryness in the summer (Table 5). However, the deterioration of skin dryness by the seasonal change to winter is considerably different between the high RR and the low RR groups.…”
Section: Discussionmentioning
confidence: 96%
“…In our previous study conducted in healthy individuals, we demonstrated that their skin barrier function on the face is impaired in winter, showing higher TEWL values, being accompanied by smaller sizes of the corneocytes obtained from the skin surface compared to those in summer, which reflects a quicker turnover rate of the epidermis probably due to irritation caused by the dry and cold winter environment [10]. In fact, low humidity itself was shown to stimulate the epidermal DNA synthesis, amplifying the hyperproliferative response of the epidermis to barrier disruption [12].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of the properties of the SC of inflammatory dermatoses have greatly improved with recent advances in non-invasive biophysical methods as well as cytological analyses of cytokines in the SC [7, 8]and the differentiation end-products such as the cornified envelope (CE) [9], enabling us to detect changes that are unrecognizable clinically. By using biophysical measurements, we have recently found that the poorly protected facial skin showed unexpected deterioration in the functional properties of the SC in the dry and cold winter time when compared with those evaluated in the warm and humid summer time in the same individuals, probably reflecting subclinical underlying inflammation [10]. Thus, we conducted a half-side test on the face to determine how facial skin changes induced by a winter environment are improved by daily applications of a moisturizing cream as assessed by non-invasive biophysical and cytological methods.…”
Section: Introductionmentioning
confidence: 99%
“…It is of note that those collected from the lesional skin of the limbs were comparable or rather larger than those found on the cheek of the normal individuals. Because the facial skin is always exposed to various kinds of environmental stimuli, we can speculate that it is in a subclinical inflammatory state even in normal individuals [26].…”
Section: Discussionmentioning
confidence: 99%